Aerogel as well as preparation method and application thereof

By using chitosan, polyvinyl alcohol and phenolic resin to prepare aerogels, the problem that existing aerogels cannot significantly improve the performance of the coating, and the effect of significantly improving the viscosity, contrast ratio, whiteness, gloss and other properties of the coating are achieved.

CN119798915APending Publication Date: 2025-04-11ASIA CUANON TECH SHANGHAI +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510015548.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

When used in coatings, existing aerogels cannot significantly improve the adhesion, penetration resistance and durability of the coatings.

Method used

Aerogel is prepared using chitosan, polyvinyl alcohol and phenolic resin as raw materials. The inter-chain fibrous structure is formed through cross-linking and condensation reactions, which improves the viscosity, contrast, whiteness, gloss, alkali resistance, scrubbing resistance and water permeability of the coating.

Benefits of technology

It significantly improves the viscosity, contrast ratio, whiteness, gloss, alkali resistance, scrubbing resistance and water permeability of the paint, and improves the overall performance of the paint.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005229804960000091
    Figure BDA0005229804960000091
  • Figure BDA0005229804960000101
    Figure BDA0005229804960000101
  • Figure BDA0005229804960000111
    Figure BDA0005229804960000111
Patent Text Reader

Abstract

The invention provides aerogel as well as a preparation method and application thereof. The aerogel is prepared from the following raw materials: chitosan, polyvinyl alcohol and phenolic resin. The aerogel is prepared by taking chitosan, polyvinyl alcohol and phenolic resin as raw materials, and when the aerogel is applied to the coating, the viscosity, contrast ratio, whiteness, gloss, alkali resistance, scrubbing resistance and water permeability of the coating can be effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of aerogels, and relates to an aerogel and a preparation method and application thereof, and specifically relates to a chitosan-polyvinyl alcohol-phenolic resin aerogel and a preparation method thereof and application thereof in coatings. Background Art

[0002] Aerogel is a new type of porous material with extremely high porosity and specific surface area, which can be used in adsorption separation, catalyst carrier, thermal insulation and other fields. In recent years, aerogel has begun to be used in coatings, mainly to improve the performance of coatings, such as improving the adhesion, anti-permeability and durability of coatings.

[0003] However, the use of existing aerogels in coatings does not significantly improve the coating's adhesion, anti-permeability and durability.

[0004] Therefore, it is expected in the art to develop an aerogel that can be used in coatings to significantly improve the performance of the coatings. Summary of the invention

[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide an aerogel and a preparation method and application thereof, and specifically to provide a chitosan-polyvinyl alcohol-phenolic resin aerogel and a preparation method thereof and application thereof in coatings. Compared with the existing common aerogels, the chitosan-polyvinyl alcohol-phenolic resin aerogel provided by the present invention can more effectively improve the viscosity, contrast ratio, whiteness, gloss, alkali resistance, scrub resistance and water permeability of the coating.

[0006] To achieve this object, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides an aerogel, wherein raw materials for preparing the aerogel include chitosan, polyvinyl alcohol and phenolic resin.

[0008] The aerogel prepared by using chitosan, polyvinyl alcohol and phenolic resin as raw materials can effectively improve the viscosity, contrast ratio, whiteness, gloss, alkali resistance, scrub resistance and water permeability of the coating.

[0009] Chitosan contains a large number of hydroxyl groups, and the molecular chain of polyvinyl alcohol also contains many hydroxyl groups. These hydroxyl groups will form hydrogen bonds and undergo cross-linking reactions, thereby forming a fibrous structure between the chains. This structure will lead to the formation of a gel system in water; chitosan also contains amino groups, carboxyl groups and acetyl groups. Phenolic resin is a polar polymer compound containing polar groups, hydroxyl groups, aldehyde groups and carboxyl groups. The amino groups in chitosan can undergo condensation reactions with the aldehyde groups in phenolic resin to produce Schiff bases; the amino groups in chitosan can also react with the carboxyl groups in phenolic resin to undergo dehydration condensation to produce peptide bonds. Because the temperature for making chitosan-polyvinyl alcohol-phenolic resin aerogel will not exceed 80°C, there are mainly two types of reactions in phenolic resin at this time. One is that the hydroxymethyl on the phenol nucleus reacts with the active hydrogen at the ortho or para position on other phenol nuclei to generate a methyne bond. The active hydrogen here comes from the free hydrogen and hydroxymethyl on the benzene ring and the hydrogen ions released by the amino group in chitosan under acidic conditions. The second type of reaction is that the generated methyne combines with the hydroxymethyl on the phenol nucleus. The structural reaction corresponds to the growth of the phenolic network skeleton. With the increase of phenolic content, agglomeration is likely to occur inside the aerogel.

[0010] Preferably, the deacetylation degree of the chitosan is ≥ 95%, for example 95%, 95.5%, 96%, 96.5%, 97%, 97.5%, 98%, 98.5%, 99%, 99.5%, etc.

[0011] Preferably, the mass ratio of chitosan to polyvinyl alcohol is (1.5-2.5):1, for example, 1.5:1, 1.6:1, 1.8:1, 2:1, 2.2:1, 2.3:1, 2.5:1, etc.

[0012] Preferably, the mass ratio of chitosan to phenolic resin is 1:(1.5-4), for example, 1:1.5, 1:2, 1:2.5, 1:3, 1:3.5, 1:4, etc.

[0013] In a second aspect, the present invention provides a method for preparing the aerogel as described in the first aspect, the preparation method comprising the following steps:

[0014] (1) mixing a phenolic resin and an organic solvent to obtain a phenolic resin solution;

[0015] (2) mixing chitosan and an organic acid aqueous solution, then adding polyvinyl alcohol and stirring to obtain a chitosan-polyvinyl alcohol solution;

[0016] (3) mixing the phenolic resin solution obtained in step (1) and the chitosan-polyvinyl alcohol solution obtained in step (2), stirring, then pouring the mixed solution into a mold, and letting it stand to obtain a chitosan-polyvinyl alcohol-phenolic resin gel;

[0017] (4) subjecting the chitosan-polyvinyl alcohol-phenolic resin gel obtained in step (3) to an aging treatment, specifically comprising: gradually heating the temperature to 60-80° C., increasing the temperature by 8-12° C. every 4 hours, sucking out the residual liquid in the mold after each heating, and adding a cleaning agent for washing;

[0018] (5) transferring the aged gel in step (4) to a carbon dioxide supercritical fluid device for drying;

[0019] (6) keeping the dried gel in step (5) warm, mixing a hydrophobic agent, water and an organic solvent to obtain a mixed solution, placing the warmed gel and the mixed solution in an oven at 70 to 80° C. for sealing treatment, and obtaining a chitosan-polyvinyl alcohol-phenolic resin aerogel, that is, obtaining the aerogel.

[0020] The present invention adopts a supercritical carbon dioxide fluid drying method to transform from gel to aerogel. The carbon dioxide fluid can effectively remove the interaction force between interfaces, reduce the damage to the gel network structure caused by capillary force, and ensure the integrity of the final aerogel to the greatest extent. Finally, the aerogel is treated by chemical vapor deposition method to improve its hydrophobic properties.

[0021] Preferably, the organic solvent in step (1) comprises ethanol.

[0022] Preferably, in step (1), based on 50 mL of the organic solvent, the amount of the phenolic resin is 8 to 12 g, such as 8 g, 9 g, 10 g, 11 g, 12 g, etc.

[0023] Preferably, the organic acid aqueous solution in step (2) comprises a citric acid aqueous solution.

[0024] Preferably, the mass fraction of the citric acid aqueous solution is 1% to 3%, for example, 1%, 1.5%, 2%, 2.5%, 3%, etc.

[0025] Preferably, in step (2), based on 100 mL of the organic acid aqueous solution, the amount of chitosan used is 2-5 g, for example, 2 g, 2.5 g, 3 g, 3.5 g, 4 g, 4.5 g, 5 g, etc.

[0026] Preferably, the stirring temperature in step (2) is 20-25°C, for example, 20°C, 21°C, 22°C, 23°C, 24°C, 25°C, etc., and the stirring time is 20-40min, for example, 20min, 25min, 30min, 35min, 40min, etc.

[0027] Preferably, the mixing in step (3) is carried out under ice bath conditions.

[0028] Preferably, in step (3), the volume ratio of the phenolic resin solution to the chitosan-polyvinyl alcohol solution is 1:(1.5-3), for example, 1:1.5, 1:2, 1:2.5, 1:3, etc.

[0029] Preferably, the stirring time in step (3) is 0.5 to 2 h, for example 0.5 h, 1 h, 1.5 h, 2 h, etc.

[0030] Preferably, the cleaning agent in step (4) comprises ethanol.

[0031] Preferably, the amount of cleaning agent added in step (4) is such that it exceeds the surface of the gel.

[0032] Preferably, the heat preservation in step (6) is carried out in an oven.

[0033] Preferably, the insulation temperature in step (6) is 30-50°C, for example, 30°C, 35°C, 40°C, 45°C, 50°C, etc., and the insulation time is 1-3h, for example, 1h, 1.5h, 2h, 2.5h, 3h, etc. The purpose of insulation is to remove liquid water inside the gel.

[0034] Preferably, the hydrophobic agent in step (6) comprises perfluorodecyltriethoxysilane.

[0035] Preferably, the amount of the hydrophobic agent in step (6) is 20% to 40% of the weight of the dried gel, for example 20%, 25%, 30%, 35%, 40%, etc.

[0036] Preferably, the organic solvent in step (6) comprises ethanol.

[0037] Preferably, the mass ratio of the hydrophobic agent, water and organic solvent in step (6) is 2:(0.8-1.2):(0.8-1.2), for example, 2:0.8:0.8, 2:0.8:1, 2:1:1, 2:1.2:1.2, etc.

[0038] Preferably, the time for the closed treatment in step (6) is 7 to 9 hours, for example, 7 hours, 7.5 hours, 8 hours, 8.5 hours, 9 hours, etc.

[0039] In a third aspect, the present invention provides a coating, which comprises the aerogel as described in the first aspect or comprises the aerogel prepared according to the preparation method as described in the second aspect.

[0040] Preferably, the coating further comprises deionized water, emulsion, filler, film-forming aid and other additives.

[0041] Preferably, the filler includes any one of heavy calcium carbonate, calcined kaolin, and aqueous kaolin, or a combination of at least two of them.

[0042] Preferably, the other auxiliary agents include any one of a pH regulator, a dispersant, a wetting agent, a bactericide, a thickener, and a defoaming agent, or a combination of at least two thereof.

[0043] Compared with the prior art, the present invention has at least the following beneficial effects:

[0044] The aerogel prepared by using chitosan, polyvinyl alcohol and phenolic resin as raw materials is used in coatings to effectively improve the viscosity, contrast ratio, whiteness, gloss, alkali resistance, scrub resistance and water permeability of the coatings. DETAILED DESCRIPTION

[0045] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0046] Unless otherwise specified, some of the raw materials used in the following examples and comparative examples of the present invention are as follows:

[0047] Chitosan: Hekouwang Biotechnology, deacetylation degree 99%;

[0048] Polyvinyl alcohol: Shanghai Guoyao, degree of polymerization is 1750±50;

[0049] Phenolic resin: Borun New Materials 2130;

[0050] Example 1

[0051] In this embodiment, a chitosan-polyvinyl alcohol-phenolic resin aerogel is provided, and the preparation method comprises the following steps:

[0052] (1) Preparation of phenolic resin solution: Dissolve 10 g of phenolic resin in 50 mL of ethanol, stir until dissolved, and set aside;

[0053] (2) Preparation of chitosan-polyvinyl alcohol solution: Dissolve 4 g of chitosan in 100 mL of 2% citric acid aqueous solution, add 2 g of polyvinyl alcohol, and stir at room temperature for 30 min to ensure thorough mixing;

[0054] (3) preparing chitosan-polyvinyl alcohol-phenolic resin gel: under ice bath conditions, the phenolic resin solution prepared in step (1) and the chitosan-polyvinyl alcohol solution prepared in step (2) were mixed at a volume ratio of 1:2, stirred for 1 hour, and then the mixed solution was poured into a mold and allowed to stand to prepare chitosan-polyvinyl alcohol-phenolic resin gel;

[0055] (4) subjecting the gel obtained in step (3) to an aging treatment, specifically comprising: gradually heating the temperature to 75° C., increasing the temperature by 10° C. every 4 hours, sucking out the residual liquid in the mold after each heating, and adding a small amount of ethanol to make it exceed the surface of the gel;

[0056] (5) transferring the aged gel in step (4) to a carbon dioxide supercritical fluid device for drying;

[0057] (6) The dried gel of step (5) is placed in an oven at 40° C. for 2 h to remove the liquid water inside, and a hydrophobic agent (perfluorodecyl triethoxysilane) of 30% by weight of the aerogel is mixed with water and ethanol in a weight ratio of 2:1:1 to obtain a mixed solution. The insulated gel and the mixed solution are placed in an oven at 70° C. for sealing treatment, and chitosan-polyvinyl alcohol-phenolic resin aerogel is obtained after 8 h.

[0058] Example 2

[0059] In this embodiment, a chitosan-polyvinyl alcohol-phenolic resin aerogel is provided, and the preparation method comprises the following steps:

[0060] (1) Preparation of phenolic resin solution: Dissolve 8 g of phenolic resin in 50 mL of ethanol, stir until dissolved, and set aside;

[0061] (2) Preparation of chitosan-polyvinyl alcohol solution: Dissolve 3 g of chitosan in 100 mL of 1.5% citric acid aqueous solution, add 2 g of polyvinyl alcohol, and stir at room temperature for 20 min to ensure thorough mixing;

[0062] (3) preparing chitosan-polyvinyl alcohol-phenolic resin gel: under ice bath conditions, the phenolic resin solution prepared in step (1) and the chitosan-polyvinyl alcohol solution prepared in step (2) were mixed in a volume ratio of 1:2, stirred for 1.5 h, and then the mixed solution was poured into a mold and allowed to stand to prepare chitosan-polyvinyl alcohol-phenolic resin gel;

[0063] (4) subjecting the gel obtained in step (3) to an aging treatment, specifically comprising: gradually heating the temperature to 70° C., increasing the temperature by 10° C. every 4 hours, sucking out the residual liquid in the mold after each heating, and adding a small amount of ethanol to make it exceed the surface of the gel;

[0064] (5) transferring the aged gel in step (4) to a carbon dioxide supercritical fluid device for drying;

[0065] (6) The dried gel of step (5) is placed in an oven at 35° C. for 2 h to remove the liquid water inside, and a hydrophobic agent (perfluorodecyl triethoxysilane) of 25% by weight of the aerogel is mixed with water and ethanol in a weight ratio of 2:0.8:1 to obtain a mixed solution. The insulated gel and the mixed solution are placed in an oven at 75° C. for sealing treatment, and chitosan-polyvinyl alcohol-phenolic resin aerogel is obtained after 7 h.

[0066] Example 3

[0067] In this embodiment, a chitosan-polyvinyl alcohol-phenolic resin aerogel is provided, and the preparation method comprises the following steps:

[0068] (1) Preparation of phenolic resin solution: Dissolve 12 g of phenolic resin in 50 mL of ethanol, stir until dissolved, and set aside;

[0069] (2) Preparation of chitosan-polyvinyl alcohol solution: Dissolve 5 g of chitosan in 100 mL of 2.5% citric acid aqueous solution, add 2 g of polyvinyl alcohol, and stir at room temperature for 40 min to ensure thorough mixing;

[0070] (3) preparing chitosan-polyvinyl alcohol-phenolic resin gel: in an ice bath, mixing the phenolic resin solution prepared in step (1) and the chitosan-polyvinyl alcohol solution prepared in step (2) at a volume ratio of 1:2, stirring for 2 h, then pouring the mixed solution into a mold and letting it stand to prepare chitosan-polyvinyl alcohol-phenolic resin gel;

[0071] (4) subjecting the gel obtained in step (3) to an aging treatment, specifically comprising: gradually heating the temperature to 80° C., increasing the temperature by 10° C. every 4 hours, sucking out the residual liquid in the mold after each heating, and adding a small amount of ethanol to make it exceed the surface of the gel;

[0072] (5) transferring the aged gel in step (4) to a carbon dioxide supercritical fluid device for drying;

[0073] (6) The dried gel of step (5) is placed in an oven at 45° C. for 2 h to remove the liquid water inside, and a hydrophobic agent (perfluorodecyl triethoxysilane) of 35% by weight of the aerogel is mixed with water and ethanol in a weight ratio of 2:1:0.8 to obtain a mixed solution. The insulated gel and the mixed solution are placed in an oven at 70° C. for sealing treatment, and chitosan-polyvinyl alcohol-phenolic resin aerogel is obtained after 8 h.

[0074] Comparative Example 1

[0075] In this comparative example, a chitosan-polyvinyl alcohol aerogel is provided, and the preparation method comprises the following steps:

[0076] (1) Preparation of chitosan-polyvinyl alcohol solution: Dissolve 4 g of chitosan in 100 mL of 2% citric acid aqueous solution, add 2 g of polyvinyl alcohol, and stir at room temperature for 30 min to ensure thorough mixing;

[0077] (2) pouring the chitosan-polyvinyl alcohol solution prepared in step (1) into a mold under ice bath conditions and allowing to stand to prepare a chitosan-polyvinyl alcohol gel;

[0078] (3) subjecting the gel obtained in step (2) to an aging treatment, specifically comprising: gradually heating the temperature to 75° C., increasing the temperature by 10° C. every 4 hours, sucking out the residual liquid in the mold after each heating, and adding a small amount of ethanol to make it exceed the surface of the gel;

[0079] (4) transferring the aged gel in step (3) to a carbon dioxide supercritical fluid device for drying;

[0080] (5) The dried gel of step (4) is placed in an oven at 40° C. for 2 h to remove the liquid water inside, and a hydrophobic agent (perfluorodecyl triethoxysilane) of 30% by weight of the aerogel is mixed with water and ethanol in a weight ratio of 2:1:1 to obtain a mixed solution. The insulated gel and the mixed solution are placed in an oven at 70° C. for sealing treatment, and chitosan-polyvinyl alcohol aerogel is obtained after 8 h.

[0081] Comparative Example 2

[0082] In this comparative example, a chitosan-phenolic resin aerogel is provided. The preparation method is different from that of Example 1 in that polyvinyl alcohol is not added in step (2).

[0083] Comparative Example 3

[0084] In this comparative example, a polyvinyl alcohol-phenolic resin aerogel is provided. The preparation method is different from that of Example 1 in that chitosan is not added in step (2).

[0085] Application Example 1

[0086] In this application example, a coating is provided, and the formula is shown in Table 1 below:

[0087] Table 1

[0088]

[0089] The preparation method comprises the following steps:

[0090] According to the formula in Table 1, the raw materials with serial numbers 1-3 are added in order, dispersed at a speed of 400 r / min for 5 minutes, then the raw materials with serial numbers 4-8 are added, the speed is slowly increased, the raw materials with serial numbers 9-14 are added, dispersed at a speed of 1800 r / min for 30 minutes, then the raw materials with serial numbers 15-22 are added, dispersed at a speed of 800 r / min for 20 minutes, to obtain the coating.

[0091] Application Examples 2 to 3, Comparative Application Examples 1 to 3

[0092] The only difference between Application Examples 2 to 3 and Comparative Application Examples 1 to 3 and Application Example 1 is that the raw material No. 13 (chitosan-polyvinyl alcohol-phenolic resin aerogel) is replaced by equal weight parts of chitosan-polyvinyl alcohol-phenolic resin aerogel provided by Examples 2 to 3 and Comparative Examples 1 to 3, respectively.

[0093] Comparative Application Example 4

[0094] The only difference between this comparative application example and application example 1 is that the raw material No. 13 (chitosan-polyvinyl alcohol-phenolic resin aerogel) is replaced by an equal weight portion of heavy calcium carbonate (Changxing Huayuan).

[0095] Comparative Application Example 5

[0096] The only difference between this comparative application example and application example 1 is that the raw material No. 13 (chitosan-polyvinyl alcohol-phenolic resin aerogel) is replaced by an equal weight portion of ordinary aerogel (silicon dioxide aerogel, Kangmai New Materials).

[0097] The coatings provided in the corresponding use cases and comparative application examples were subjected to performance tests, and the performance test methods were based on GB / T9756-2018 "Synthetic resin emulsion interior wall coatings".

[0098] The performance test results are shown in Table 2.

[0099] Table 2

[0100]

[0101]

[0102] It can be seen from Table 2 that the coatings prepared using the chitosan-polyvinyl alcohol-phenolic resin aerogel provided by the embodiments of the present invention have higher viscosity (100.2-103.9 ku), higher contrast ratio (96.62%-96.90%), higher whiteness (92.1%-92.5%), higher gloss, excellent alkali resistance (all without abnormalities), excellent scrub resistance (scrub resistance: 19000-20500 times), and excellent water permeability resistance (1.2-1.4 mL).

[0103] Compared with Application Example 1, chitosan-polyvinyl alcohol aerogel is added in Comparative Application Example 1, and the scrub resistance of the provided coating becomes worse. Due to the lack of phenolic resin, the scrub resistance of the coating is greatly reduced, and the viscosity, contrast ratio, gloss, alkali resistance and water permeability of the coating are all reduced; chitosan-phenolic resin aerogel is added in Comparative Application Example 2, and the viscosity and water permeability of the provided coating are reduced, and the scrub resistance and contrast ratio are slightly reduced; polyvinyl alcohol-phenolic resin aerogel is added in Comparative Application Example 3, and the viscosity of the provided coating is significantly reduced. Since chitosan has a thickening effect, the lack of chitosan leads to a significant reduction in viscosity, and the water permeability of the coating is also reduced.

[0104] Compared with Application Example 1, in Comparative Application Example 4, no aerogel is added, and the viscosity, contrast ratio, gloss, scrub resistance and water permeability resistance of the coating are all deteriorated.

[0105] Compared with Application Example 1, in Comparative Application Example 5, by adding ordinary aerogel, the viscosity, contrast ratio, whiteness, gloss, alkali resistance, scrub resistance and water permeability resistance of the coating all deteriorated.

[0106] The applicant declares that the present invention illustrates the aerogel and its preparation method and application through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. An aerogel, characterized in that: The raw materials for preparing the aerogel include chitosan, polyvinyl alcohol and phenolic resin.

2. The aerogel according to claim 1, characterized in that The deacetylation degree of the chitosan is ≥95%; Preferably, the mass ratio of chitosan to polyvinyl alcohol is (1.5-2.5):1; Preferably, the mass ratio of chitosan to phenolic resin is 1:(1.5-4).

3. A method for preparing aerogel according to claim 1 or 2, characterized in that: The preparation method comprises the following steps: (1) mixing a phenolic resin and an organic solvent to obtain a phenolic resin solution; (2) mixing chitosan and an organic acid aqueous solution, then adding polyvinyl alcohol and stirring to obtain a chitosan-polyvinyl alcohol solution; (3) mixing the phenolic resin solution obtained in step (1) and the chitosan-polyvinyl alcohol solution obtained in step (2), stirring, then pouring the mixed solution into a mold, and letting it stand to obtain a chitosan-polyvinyl alcohol-phenolic resin gel; (4) subjecting the chitosan-polyvinyl alcohol-phenolic resin gel obtained in step (3) to an aging treatment, specifically comprising: gradually heating the temperature to 60-80° C., increasing the temperature by 8-12° C. every 4 hours, sucking out the residual liquid in the mold after each heating, and adding a cleaning agent for washing; (5) transferring the aged gel in step (4) to a carbon dioxide supercritical fluid device for drying; (6) keeping the dried gel in step (5) warm, mixing a hydrophobic agent, water and an organic solvent to obtain a mixed solution, placing the warmed gel and the mixed solution in an oven at 70 to 80° C. for sealing treatment, and obtaining a chitosan-polyvinyl alcohol-phenolic resin aerogel, that is, obtaining the aerogel.

4. The preparation method according to claim 3, characterized in that: The organic solvent in step (1) comprises ethanol; Preferably, in step (1), based on 50 mL of the organic solvent, the amount of the phenolic resin is 8 to 12 g.

5. The preparation method according to claim 3 or 4, characterized in that: The organic acid aqueous solution in step (2) comprises a citric acid aqueous solution; Preferably, the mass fraction of the citric acid aqueous solution is 1% to 3%; Preferably, in step (2), the amount of chitosan used is 2 to 5 g based on 100 mL of the organic acid aqueous solution; Preferably, the stirring temperature in step (2) is 20 to 25° C., and the stirring time is 20 to 40 min.

6. The preparation method according to any one of claims 3 to 5, characterized in that: The mixing in step (3) is carried out under ice bath conditions; Preferably, in step (3), the volume ratio of the phenolic resin solution to the chitosan-polyvinyl alcohol solution is 1:(1.5-3); Preferably, the stirring time in step (3) is 0.5 to 2 hours.

7. The preparation method according to any one of claims 3 to 6, characterized in that: The cleaning agent in step (4) comprises ethanol; Preferably, the amount of cleaning agent added in step (4) is such that it exceeds the surface of the gel.

8. The preparation method according to any one of claims 3 to 7, characterized in that: The heat preservation in step (6) is carried out in an oven; Preferably, the insulation temperature in step (6) is 30 to 50° C., and the insulation time is 1 to 3 hours; Preferably, the hydrophobic agent in step (6) comprises perfluorodecyltriethoxysilane; Preferably, the amount of the hydrophobic agent in step (6) is 20% to 40% of the weight of the dried gel; Preferably, the organic solvent in step (6) comprises ethanol; Preferably, the mass ratio of the hydrophobic agent, water and organic solvent in step (6) is 2:(0.8-1.2):(0.8-1.2); Preferably, the time for the closed treatment in step (6) is 7 to 9 hours.

9. A coating, characterized in that: The coating comprises the aerogel according to claim 1 or 2, or comprises the aerogel prepared according to the preparation method according to any one of claims 3-8.

10. The coating according to claim 9, characterized in that The coating also includes deionized water, emulsion, filler, film-forming aid and other additives; Preferably, the filler comprises any one of heavy calcium carbonate, calcined kaolin, and aqueous kaolin, or a combination of at least two thereof; Preferably, the other auxiliary agents include any one of a pH regulator, a dispersant, a wetting agent, a bactericide, a thickener, and a defoaming agent, or a combination of at least two thereof.